Metabolic signatures of metabolic dysfunction-associated steatotic liver disease in severely obese patients - Babu, Ambrin Farizah; Palomurto, Saana; Kärjä, Vesa; Käkelä, Pirjo; Lehtonen, Marko; Hanhineva, Kati; Pihlajamäki, Jussi; Männistö, Ville (Elsevier Inc., 2025)
Backround
Metabolic dysfunction-associated steatotic liver disease (MASLD) can lead to liver fibrosis, cirrhosis, and hepatocellular carcinoma. Still, most patients with MASLD die from cardiovascular diseases indicating metabolic alterations related to both liver and cardiovascular pathology.
Aims and Methods
The aim of this study was to assess biologic pathways behind MASLD progression from steatosis to metabolic dysfunction-associated steatohepatitis (MASH) using non-targeted liquid chromatography-mass spectrometry analysis in 106 severely obese individuals (78 women, mean age 47.7 7 ± 9.2 years, body mass index 41.8 ± 4.3 kg/m²) undergoing laparoscopic Roux-en-Y gastric bypass.
Results
We identified several metabolites that are associated with MASLD progression. Most importantly, we observed a decrease of lysophosphatidylcholines LPC(18:2), LPC(18:3), and LPC(20:3) and increase of xanthine when comparing those with steatosis to those with MASH. We found that indole propionic acid and threonine were negatively correlated to fibrosis, but not with the metabolic disturbances associated with cardiovascular risk. Xanthine, ketoleucine, and tryptophan were positively correlated to lobular inflammation and ballooning but also with insulin resistance, and dyslipidemia, respectively. The results did not change when taking into account the most important genetic risk factors of MASLD.
Conclusions
Our findings suggest that there are several separate biological pathways, some of them independent of insulin resistance and dyslipidemia, associating with MASLD.